Monolayer hexagonal arsenene with tunable electronic structures and magnetic properties via impurity doping. Issue 2 (14th December 2015) - Li, Zhongjun; Xu, Wei; Yu, Yuanqin; Du, Hongyang; Zhen, Kun; Wang, Jun; Luo, Linbao; Qiu, Huaili; Yang, Xiaobao
Abstract : In this study, by using density functional theory, we have theoretically investigated the electronic and magnetic properties of x-substituted hAs (x = B, C, N, O, Ga, Ge, Se, and monovacancy) and x-adsorbed hAs (x = As). Abstract : Monolayer hexagonal arsenene (hAs), a typical two-dimensional semiconducting material with a wide band gap and high stability, has attracted increasing research interest due to its potential applications in optoelectronics. Using first-principles calculations, we have investigated the electronic and magnetic properties of x-substituted hAs (x = B, C, N, O, Ga, Ge, Se, and monovacancy) and x-adsorbed hAs (x = As). Our results show that the B-, N-, and Ga-substituted hAs have spin-unpolarized semiconducting characters like pristine hAs, and indirect–direct band gap transitions are induced in the B- and N-substituted systems. In contrast, the O-, Se-, and monovacancy-substituted hAs are metallic, and the C- and Ge-substituted hAs show spin-polarized semiconducting characters with band gaps of 1.1 and 1.3 eV for the spin-up channels and 1.0 and 0.7 eV for the spin-down channels, respectively. For the As-adsorbed hAs, the Fermi level crosses the spin-up states, yielding metallic behavior, while the spin-down channel retains semiconducting character. Detailed analysis of electronic structures for the C-substituted, Ge-substituted, and As-adsorbed hAs shows that strong hybridizations between the doping atoms and As atoms lead to energy splitting near the Fermi level and consequently induce magnetic moments. By selective doping, hAs can be transformed from a spin-nonpolarized semiconductor to a spin-polarized semiconductor, to a half-metal, or even to a metal, which indicates that the doped hAs will have promising potential in future electronics, spintronics, and optoelectronics.